The Special Conditions for the Crime of Extradition in Accordance With International Law Provisions and Iraqi Law - المالكي, هادي نعيم; عبد الحميد, سارة ظافر (Journal of Legal Sciences, 2019)
The title of this research is "The Special Conditions for the Crime of Extradition in Accordance With International Law Provisions and Iraqi Law." The examination of the conditions of extradition is of paramount importance because it establishes the general provisions on the basis of which extradition is made, if such conditions are met at the time of the issuing of the extradition decision. Crimes vary according to their types, gravity and description. For this reason, the conditions for determining the crimes in which extradition is permissible have been established. These conditions are that the crime committed is of a certain gravity. The second condition is dual criminality in the requesting State and the States to be extradited; the third condition is that the offense is an extraditable offense, and there are certain limitations of the offenses for which extradition may be extraditable.